O negro e a educação : movimento e política no Estado do Rio Grande do Sul : 1987-2001 - Adão, Jorge Manoel (2002)
This Master Research is a boarding of the public politics in education of blacks in Rio Grande do Sul State, realized since the praxis, performance, proposal and organization of the entities and groups that constitute the gaúcho black movement, for the Project “The Black and the Education” of the Educational Secretary of State and “Advice of Development Participation and of the Black Community of the Rio Grande do Sul State”: public-institutional spaces created with the task to implement and to develop public black-educative politics. This Master Research has this theoretical reference as the black-Brazilian paradigm which unites the afrocentricity, blackness and affirmative actions, as reflexive and concrete form of incrementation of these public politics; and my experience and black militancy with an eye challenge that bring up-to-date an epistemological perspective where the researcher constitutes himself as the subject and the object, involved in this reality, at the same time.